2016
DOI: 10.1016/j.apcata.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnO-loaded Co0.85Se nanocomposites and their enhanced performance for decomposition of hydrazine hydrate and catalytic hydrogenation of p-nitrophenol

Abstract: Nanocomposite is a kind of multiphase solid materials with nano-dimensional. It generally displays more preferable performance than its corresponding single precursors or conventional composite materials due to size effect and interfacial effect. Herein, we report the synthesis of a kind of nanocomposite via one pot route without using any surfactant or structure-directing agents. The structure, composition and morphology of the as-synthesized products were characterized by XRD, XPS, SEM, TEM and BET surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The experiments utilized a Jasco V-730 spectrophotometer whose sample compartment was retrofitted with sample holders able to support 38 mL Borofloat 33 floated borosilicate flat glass cuvettes with a 2.5 cm path length (Specialty Glass ProductsWillow Grove, PA). For each reaction, three 8 mL solutions were prepared: (i) 150 μM 4-NP, (ii) NaBH 4 (6,9,12,15,30,45,60,75 or 90 mM), and (iii) Au catalysts (0.324, 0.648, or 1.626 μM). All three solutions utilized DI water with the ambient dissolved oxygen content, but for the case of the Au catalyst, the stock solution was deaerated.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The experiments utilized a Jasco V-730 spectrophotometer whose sample compartment was retrofitted with sample holders able to support 38 mL Borofloat 33 floated borosilicate flat glass cuvettes with a 2.5 cm path length (Specialty Glass ProductsWillow Grove, PA). For each reaction, three 8 mL solutions were prepared: (i) 150 μM 4-NP, (ii) NaBH 4 (6,9,12,15,30,45,60,75 or 90 mM), and (iii) Au catalysts (0.324, 0.648, or 1.626 μM). All three solutions utilized DI water with the ambient dissolved oxygen content, but for the case of the Au catalyst, the stock solution was deaerated.…”
Section: ■ Methodsmentioning
confidence: 99%
“…41 The small peak at 53.4 eV corresponds to Fe 3p, and the peaks at 58.4 and 60 eV originate from Co 3p 3/2 and Co 3p 1/2 , respectively, suggesting the presence of Co−Se and Fe−Se binding. 42 The S5a2). These peaks are, respectively, assigned to the metal oxides (M−O) and the adsorbed oxygen species FeFe@CoFe into hollow CoFe-PBA.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The two peaks centered at 53.7 and 54.6 eV (Se 3d 5/2 and Se 3d 3/2 ) are attributed to the selenide species, whereas the peak at 55.6 eV corresponds to the metal-state Se . The small peak at 53.4 eV corresponds to Fe 3p, and the peaks at 58.4 and 60 eV originate from Co 3p 3/2 and Co 3p 1/2 , respectively, suggesting the presence of Co–Se and Fe–Se binding …”
Section: Resultsmentioning
confidence: 99%
“…Multiphase solid materials with nano-dimensional ZnO particles have also been used for the development of effective sensors for hydrazine molecules. These multiphase solid materials with ZnO have a direct influence on their size, interfacial properties, and electrocatalytic activities against harmful analytes [ 58 ]. It was found that most of the electrochemical-based sensing of hydrazine molecules using ZnO nanoparticles have mainly used nafion for the tight attachment of ZnO nanomaterials on the surface of gold electrodes.…”
Section: Chemical Sensing Applications Of Zno Nanomaterialsmentioning
confidence: 99%